Antineoplastic chemotherapy and congenital tooth abnormalities in children and adolescents - Krasuska-Sławińska, Ewa; Brożyna, Agnieszka; Dembowska-Bagińska, Bożenna; Olczak-Kowalczyk, Dorota (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Chemotherapeutic treatment in children and adolescents carries a risk of congenital tooth disorders and dentinoma. Study objective is to assess the correlation between tooth abnormalities, early complications of multidrug chemotherapy, and chemotherapeutics used in different antineoplastic therapies in children and adolescents. Material and methods : Enamel defects (developmental defects of enamel index – DDE index) and defects in tooth number, size, and structure were assessed clinically and radiologically in 60 patients who underwent chemotherapy on average 4.9 ±3.4 years earlier (PCH), and 60 generally healthy subjects (control group – CG), aged 6–18 years. Höltta’s defect index (DeI) was calculated. Medical files provided information on neoplasm type, age at treatment start and chemotherapy duration, chemotherapeutic type and dose, vomiting, and mucositis (CTCAE v4.0). Statistical significance of differences between groups was assessed with the Mann-Whitney U test and the correlation between dental defects and chemotherapy with Spearman’s rank correlation coefficient (significance p ≤ 0.05). Results: Enamel defects, tooth agenesis, microdontia, root resorption, taurodontism, and dentinoma occurred statistically significantly more often in the PCH group. A correlation was established between vincristine use and dose and all types of dental defects; cyclophosphamide, doxorubicin, and isophosphamide and hypodontia; microdontia, root resorption, and enamel defects; etoposide and cisplatin and microdontia, root resorption, and enamel defects; methotrexate root resorption and enamel defects; carboplatin and dentinoma and enamel defects. Mucositis and vomiting promoted root resorption, microdontia, and enamel defects. Conclusions : Dental defects are related to both the use of respective chemotherapeutics, especially vincristine, cyclophosphamide, doxorubicin, and isophosphamide, and to early complications in multidrug chemotherapy – mucositis and vomiting. Vincristine and carboplatin use may promote dentinoma.